Effects of Human Resources Training on Employee Perceived Performance: Comparison of Somalia-Turkiye Telekommunication Bussinesses - Abdulahi, Burhan; AYKAN, Ebru (Archives of Business Research, 2016)
The present study was conducted to investigate the effects of human resources training on employee perceived performance in telecommunication business and to compare such relations in two businesses operating in Somali and Turkey. The research was conducted on 240 participants employed in a telecommunication organization operating Galkio province of Somali (Golis Telekom) and a telecommunication organization operating in Kayseri province of Turkey (Türk Telekom). Current findings revealed that there were significant relationships between human resources training and perceived performance of employees and human resources training had significant impacts on perceived performance of employees. It was also observed that average training level and performance of Türk Telekom employees were higher than the employees of Golis Telekom and the differences in their training levels and performances were found to be significant